Rheological and fibrinolytic findings in multiple sclerosis. Issue 4 (April 1981) - Brunetti, A; Ricchieri, G L; Patrassi, G M; Girolami, A; Tavolato, B
Abstract : Blood viscosity indices, fibrinolytic activity and other serum proteins related to haemocoagulation have been studied in 36 patients with multiple sclerosis. The whole blood viscosity was found to be increased in multiple sclerosis. The increase was caused by a decrease in erythrocyte deformability since plasma viscosity and haematocrit were normal. Plasminogen, fibrinogen and alpha 2 antitrypsin levels were found to be lower than normal. Such alterations were not observed in a group of patients with other non-immunological neurological diseases. In the latter group some coagulation indices were even higher than normal. The higher mean age of the pathological controls could explain the observed levels. The abnormalities observed in multiple sclerosis patients are considered to be a consequence of a non-specific activation of the coagulative system in a chronic immunological disease.